Ethnomathematics in the culture of mountain rice farming of the Dayak Kanayatn community - Yudiani Linling; Nuryadi Nuryadi (Universitas negeri Yogyakarta, 2022)
Rice is the staple food for people in West Kalimantan. One of the regions with rice farming culture is the Tunang village in Mempawah Hulu sub-district, Landak district, West Kalimantan, which is influenced by the habits of the population and geographical location. There are a series of processes for growing rice in the village that are inseparable from culture and can be linked to mathematics (ethnomathematics). The objective of this study is to identify the ethnomathematics of the cultivation of mountain rice or moton rice in the Dayak Kanayatn tribe, especially the Dayak Ahe tribe. This study uses a qualitative approach with a descriptive method. Data collection techniques include literature studies, surveys, and interviews. The results show that rice farming activities in the Dayak Ahe community include clearing the land (nabas uma), cutting down trees (nabang), burning the field (nunu uma), cleaning the field after the burning (marasehan uma), sowing (nugal uma), weeding (ngarumput uma), and harvesting the rice (bahanyi). These processes are accompanied with a series of ritual ceremonies, namely nabo’ panyugu nagari, nabo’ panyugu tahutn/naik dango, ngawah, batanam padi (which consists of ngalabuhatn, ngamalo lubakng tugal, and ngiliratn panyakit padi), ngaladakng buntikng padi, ngabati’, and ngaleko. There are ethnomathematics values contained in the ceremonies, namely points and lines, three-dimensional figures, two-dimensional shapes, counting, and symmetry of shape.